Interactions between stereotype threat, subjective aging, and memory in older adults. Issue 1 (2nd January 2019) - Marquet, Manon; Missotten, Pierre; Dardenne, Benoit; Adam, Stéphane
ABSTRACT: This study examined whether the effects of stereotype threat on memory and subjective age were moderated by positive age stereotypes and self-perceptions of aging among older adults. Perceived threat as a mechanism underlying these effects was also explored. Results showed that stereotype threat (high vs. low threat) did not affect the dependent variables. Moreover, self-perceptions of aging did not moderate the effect of stereotype threat on the dependent variables. However, for people with more positive age stereotypes, older people under highthreat perceived more threat than people under low threat. This could be explained by an effect of age stereotypes in the high-threat group: the more positive age stereotypes held by participants, the more they perceived threat, which in turn decreased their memory performance and made them feel mentally older. We hypothesized that age group identity is stronger in people with more positive age stereotypes, which increase perceived threat.